Enhancing Detection of Hidden Injuries: Evaluating the Precision of Abdominal Ultrasound as a Supplementary Tool in Penetrating Trauma Evaluation - Fatmah Mohammed Mousa, Ehtisham Mohammed Alahmari, Abdullah, Hassan Ahmed Qhal, Abdulaziz Abdullah Alhazzaa, Norah Abdullah Aldakhil, Hanan Ibrahim Alamoudi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Systematic Sonography Looking for Occult Wounds (SSLOW) represents a novel approach in trauma evaluation, specifically targeting the detection of intra-abdominal injuries in cases of penetrating trauma. Despite its potential significance, there remains a dearth of empirical evidence regarding its effectiveness. This study endeavors to evaluate the accuracy and efficacy of the SSLOW examination in this context.Methods: Conducted over a span of 10 months, this prospective case series was carried out at the Accident and Emergency Department (A&E) . Enrolled participants comprised individuals aged 16 years and above who presented to the A&E department with penetrating abdominal trauma. Initial assessment involved the performance of an E-FAST examination for all patients. Subsequently, in cases where the E-FAST results were negative, a SSLOW examination was conducted. Specifically, the sonographer focused on identifying any evidence of free fluid accumulation amidst the loops of bowel. The outcomes of the SSLOW examination were then compared with the standard care procedures, including surgical consultation, serial abdominal and E-FAST examinations, laparotomy, and a 7-day follow-up period. The results were categorized into true positives, false positives, true negatives, and false negatives, facilitating the calculation of sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratios.Results: Among the participants, there were 5 (12%) true positives, 1 (2%) false positive, 37 (86%) true negatives, and zero (0%) false negatives. SSLOW exhibited a sensitivity of 100% (95% CI 5–100%) and a specificity of 97% (95% CI 74–96%). The positive predictive value was determined to be 80% (95% CI 1.0–64%), while the negative predictive value was found to be 100% (95% CI 88–100%). Furthermore, the positive likelihood ratio was calculated as 8.4 (95% CI 3.69–19.1), with a negative likelihood ratio of 0.Conclusion: The findings of this study suggest that the SSLOW examination holds promise as a valuable adjunct in the comprehensive assessment of penetrating abdominal injuries.